Does Corporate Environmental Performance Influence Investors’ Share Ownership? Evidence from the FTSE/JSE Responsible Investment Index - Siwela, Witness (International Journal of Economics and Financial Issues, 2025)
A plethora of recent studies posit high relevance to the investigation of the impact that environmental, social and governance (ESG) has on investors’ economic decisions. Notwithstanding the notable contribution that these prior studies have brought to the fore, the extant literature reviewed points to gaps emanating from disjointed literature and scanty results. To this end, there is no doubt from emerging research that capital lenders tend to expect a higher return premium for substandard corporate environmental performance. Such demands are exacerbated by environmental risks and hefty litigations linked to poor ESG ratings. However, this paper becomes imperative given the prevailing need to clarify the position of equity holders regarding ESG disclosures. This paper is presented in the context of investors having to make investment decisions amid questionable credibility of ESG disclosures. Therefore, we seek to establish the short run and long run dynamics between corporate environmental performance (hereafter named as CEP) and investors’ share ownership (hereafter named as InvSO). We target companies listed in the FTSE/JSE Responsible Investment Index (hereafter named as FTSE/JSE RII) to draw a sample of 21 companies using purposive sampling technique. In addition to that, archival data were collected to compute a short panel data set. Thus, panel data set employed for statistical analysis comprised of 21 cross sections of 6 years totalling 126 observations. Thereafter, the paper adopted first differenced econometric models in data analyses namely panel vector error correction model (VECM), and subsequently panel least squares (PLS), Wald Test, and impulse response functions (IRF). The results indicated that a statistically significant positive relationship exist in the long run between corporate environmental performance and investors’ share ownership. On the contrary, the same endogenous variables produced a statistically significant negative relationship in the short run. The paper contributes new insights to the prevailing debate regarding investors’ perceptions on ESG practices, renders clarity to extant literature on the subject and equips companies on best practices for luring prospective equity investors.